Book Review Guide to Blended Learning, by Marta Cleveland: Innes with Dan Wilton, Common Wealth of Learning (COL) Canada, 2018 - Sridevi, K V (Voices of Teachers and Teacher Educators, 2020)
It is very essential to relook the entire teaching learning process to help the students to learn better and develop into 21st century global citizens. Teachers need to empower themselves with skill sets that are essential to conduct teaching learning online along with face to face teaching. In this context, this book prepares an individual for the complex world of digital or online classroom also and face to face interaction in a blended mode.